Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.4269/ajtmh.2002.66.186
|View full text |Cite
|
Sign up to set email alerts
|

Modeling relationships between climate and the frequency of human plague cases in the southwestern United States, 1960-1997.

Abstract: Abstract. The relationships between climatic variables and the frequency of human plague cases were modeled by Poisson regression for two adjoining regions in northeastern Arizona and northwestern New Mexico. Model outputs closely agreed with the numbers of cases actually observed, suggesting that temporal variations in plague risk can be estimated by monitoring key climatic variables, most notably maximum daily summer temperature values and time-lagged (1 and 2 year) amounts of late winter (February-March) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(170 citation statements)
references
References 52 publications
7
158
0
3
Order By: Relevance
“…Our findings corroborate those of other studies on temporal associations with human plague incidence [18][19][20] . Parmenter et al 21 found that the cyclical pattern of the annual distribution of plague cases in New Mexico (USA) was associated with fluctuations in the rodent population or in the rodents' responses to environmental variations such as food and shelter availability.…”
Section: Yearsupporting
confidence: 83%
“…Our findings corroborate those of other studies on temporal associations with human plague incidence [18][19][20] . Parmenter et al 21 found that the cyclical pattern of the annual distribution of plague cases in New Mexico (USA) was associated with fluctuations in the rodent population or in the rodents' responses to environmental variations such as food and shelter availability.…”
Section: Yearsupporting
confidence: 83%
“…In situations where flea loads differed among time periods, they generally increased during the months of early rains or agricultural harvest periods from March through August as the plague season approached. These changes could be driven by climate, as has been suggested for plague activity in this and other geographic regions, 8,[41][42][43][44] and could prime vector-host communities for plague epizootics, if the pathogen is introduced. The onset of heavy rains in late August, which marks the start of the plague season, could drive rats into human dwellings, which may increase the likelihood of human exposure to infected rats or their fleas.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we believe such an association with agricultural intensity and plague case occurrence is biologically plausible. According to a trophic cascade hypothesis, [35][36][37] areas with increased primary production of food crops may increase the carrying capacity of rodents. Several quantitative models have demonstrated that the probability of plague epizootics, which represent periods when humans are at greatest risk for exposure to infectious fleas, 38 is dependent on reaching critical thresholds of key rodent hosts.…”
Section: Discussionmentioning
confidence: 99%